RANCANG BANGUN KAMUS BAHASA JAWA BREBES – SUNDA BERBASIS ANDROID - Sugiyamta, Sugiyamta; Annisa Rahmawati, Nur (Information Technology and Telematics, 2018)
Abstract - the existence of two languages in one area such in Brebes is being an issue that quite annoying. because with the existence of these two languages, makes communication between poeple who speak javanese and sundanese became difficult, so if two people with different languages meet and want to communicate they use indonesian. if that continues then it is possible the two languages of the region will be vanish from the generation to next generation. In this thesis, the author tries to analyze the basic problems and try to provide another alternative in preserving the language of the area which are also be introduced to other areas. author use SDLC systems development methods. Designing process models using UML (Unified Modeling Language). The resulting application is android based that is used to find the vocabulary of javanese and sundanese with the description given in indonesian language. this application also helps a person to translate the words he want to say to the others.